FACTORS INHIBITING THE ENFORCEMENT OF THE CRIMINAL LAW OF SEXUAL ABUSE OF CHILDREN (STUDY OF DECISION NUMBER 158/PID.SUS/2020/PN TGT) - Gafur Irfianto; Rahandy Rizki Prananda (Universitas Muhammadiyah Ponorogo, 2023)
The crime of copulation is a sensitive issue, especially if the victim is a minor, which can result in impaired mental growth in the future. This study aims to analyze the application of criminal sanctions for child copulation by women and child protection activists (Verdict Study Number 158 / Pid.Sus / 2020 / PN Tgt) and other significant factors that affect law enforcement against perpetrators of criminal acts of copulation against children. The type of research in this research is a normative juridical method whose other name is doctrinal legal research, also known as library research or document studies, because this research is carried out or aimed only at written regulations or other legal materials. The approaches used by researchers in compiling this research are, among others: Statue Approach and the Case approach. The results showed that the implementation of criminal sanctions for criminal acts of child copulation by activists to protect women and children against children had been carried out by the provisions of the applicable laws and regulations. Factors that hinder law enforcement against perpetrators of criminal acts of copulation against children who are victims of trafficking by women and child protection activists in Paser Regency are law enforcement factors, community factors, and cultural factors.